Islamic Music In Banyuwangi: Artists’adaptation After The 1965 Political Violence - Nurullita, Hervina (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This study examines the adaptation strategies of Banyuwangi artists in musical practices after the 1965 political violence. The stigma attached to the song Genjer-genjer and its allegedly association with the Indonesian Communist Party (PKI) affected the local art scene. The research applies the historical method through heuristics, source criticism, interpretation, and historiography. The findings revealed that Banyuwangi musicians shifted their repertoire from social themes to Islamic genres. This transformation constructed a socio-religious identity that protected them from political accusations and sustained local musical traditions. The study highlights music as both a cultural expression and a survival strategy under repressive conditions.